Usage and cost of first-line drugs for patients referred to inpatient anthroposophic integrative care or inpatient conventional care for stress-related mental disorders—a register based study. Issue 1 (December 2015) - Sundberg, Tobias; Hussain-Alkhateeb, Laith; Falkenberg, Torkel
Abstract Background Stress-related mental disorders (SRMD) are common and costly. Rehabilitation strategies, including pharmacotherapy, may be complicated to evaluate. Previous research has indicated increased quality of life and self-rated health for SRMD patients that receive a combination of conventional and complementary therapies, i.e. integrative care. The aim of this retrospective registry study was to explore and contrast the prescription of first-line drugs for SRMD patients referred to hospital inpatient anthroposophic integrative care (AIC) or inpatient conventional care (CC). Methods SRMD patients that had received AIC or CC were identified through high-quality inpatient registry data from Stockholm County Council and matched by available background characteristics including diagnosis (ICD-10: F43), age, gender and socio-economics. General disease load was estimated by analysis of ICD-10 chapter data. The Swedish Prescribed Drug Register was then used to investigate purchased defined daily doses (DDD) and cost of drugs from 90-days before/after, and 180-days before/after, the first visits (index) to AIC and CC respectively. First-line drug categories were Anatomical Therapeutic Chemical classification codes N05A (antipsychotics), N05B (anxiolytics), N05C (hypnotics and sedatives) and N06A (antidepressants). Results There were no statistically significant differences between the AIC (n  = 161) and the CC (n  = 1571) cohorts in terms of background characteristics and the overall disease loads were similar between the groups the preceding year. At baseline, the prescription of first-line anxiolytics and antidepressants were not statistically different between groups whereas the prescription of antipsychotics and hypnotics/sedatives were lower for the AIC cohort. The overall change in drug prescriptions and costs during the investigated periods, both for the 90-days before/after and for the 180-days before/after the index visit, showed a general decrease within the AIC cohort with significantly less prescribed anxiolytics and hypnotics/sedatives. During the same time periods there was a general increase in prescriptions and costs of first-line drugs within the CC cohort. The overall disease loads were generally stable within both cohorts over time, except that the CC cohort had increased visits registered with an ICD-10 F-chapter diagnosis the year after index. Conclusions The results suggests that there may be different drug utilization patterns for SRMD patients referred to AIC or CC. Different management strategies between AIC and CC providers, different SRMD disease severities and different preferences of patients referred to AIC and CC are hypothetical differentiating factors that may influence drug outcomes over time. Additional studies including prospective and randomized clinical trials are warranted to determine if there is a causal link between inpatient AIC and reduced drug utilization.